Core Concepts in Hypertension in Kidney Disease edited by Ajay K. Singh, Rajiv Agarwal. - Singh, Ajay K.; Singh, Ajay K.; Agarwal, Rajiv.; Agarwal, Rajiv. (Springer New York : Imprint: Springer, 2016)
This guide provides a comprehensive review of the full spectrum of hypertension in chronic kidney disease (CKD). Targeted towards the busy practitioner, the focus of this volume is on various therapies and how to lower blood pressure through lifestyle changes. Specialist patient populations and hypertension and causes of hypertension are also covered in detail. Clinically-focused and authoritative, this resource offers a rationalized approach to diagnosing and treating hypertension in CKD.